P143 A Retrospective Study of Echocardiography and Follow-Up After Acute Pulmonary Embolism – Are We Missing Chronic Thromboembolic Pulmonary Hypertension?. (19th November 2012) - Slim, D; McBrien, CN; O'Sullivan, LM; Message, SD; Raghuram, A
Abstract : Introduction: Pulmonary Hypertension (PH) is defined as raised Pulmonary Arterial Systolic Pressure ≥25mmHg at rest on Right Heart Catheterisation. 1 Chronic Thromoboembolic Pulmonary Hypertension (CTEPH) is a recognised complication of pulmonary embolism (PE), with a reported annual cumulative incidence of 3.1%. 2 Patients with evidence of PH or Right Ventricular Dysfunction (RVD) during admission should be referred for echocardiography usually 3–6 months after discharge to establish PH resolution. 1 Objective: To identify patients at risk of CTEPH, evaluate their follow-up plans and establish the proportion with evidence of acute RVD/PH who are investigated for persistent PH. Methods: Retrospective analysis of all diagnoses of PE on Computed Tomography Pulmonary Angiography (CTPA) in 2010 in a single Trust. Patients were stratified according to size and location of PE, and any reported radiological evidence of RVD. Echocardiography reports were reviewed for evidence of PH. Results: 19.3%(329/1702) of CTPA scans revealed PE: Massive (28.6%); Submassive (28.0%); Peripheral (44.4%). Only 17.6%(58/329) had inpatient echocardiography, with 55.1%(32/58) suggesting PH (PASP≥ 36 mmHg). 78.1%(25/32) of these patients survived to 6 months and follow-up echocardiography was performed within 6 months for 40%(10/25) of this subset. Overall, 80.9% (266/329) of patients with confirmed PE survived past 6 months. Follow-up echocardiogram was performed within 6 months on 20.3% (54/266) of survivors; PH was demonstrated in 18.5%(10/54). RV strain was reported in 15.2% (50/329) of CTPA scans. Follow-up echocardiogram was performed within 6 months on 19.5% (8/41) of those alive at 6 months. 84.2%(154/183)of individuals diagnosed with a massive or submassive PE survived to 6 months. Respiratory or cardiology follow-up was planned for 23% (36/154). Conclusions: Our findings suggest follow-up after acute PE is suboptimal, potentially missing early PH due to a low number of early echocardiograms. The relatively high percentage of PH on echocardiography compared to reported rates is likely due to selection bias. The results suggest there may be a missed cohort at risk of developing PH, i.e. those with RV strain on CTPA or high thrombus load, being denied early or more aggressive interventions such as pulmonary endarterectomy. References: Galié et al. EurRespirJ 2009; 34:1219–63. Pengo et al. NEJM 2004; 350 :2257–64.